The state, people, and zombie outbreak: Foucauldian reading of Zona Merah series - Agung, Lingga; Wismoyo, Erlana Adli; Adi, Anggar Erdhina (Universitas Padjadjaran, 2026)
Background: Indonesian horror cinema has long relied on local ghost figures, while zombies often appear as a borrowed form with weaker cultural intimacy. Zona Merah (2024), a Vidio Original series, becomes a strategic case because it shifts horror from the supernatural to a politically managed emergency, where governance operates through discourse, media visibility, and securitized control. Purpose: This study examines how Zona Merah represents the relationship between the state, the people, and the zombie outbreak, and how it articulates post-Reformasi local power through dynastic politics, oligarchic networks, and institutional capture under crisis conditions. Methods: This qualitative study applies scene-based textual analysis combined with Foucauldian discourse analysis. The primary data consists of all eight episodes of Season 1, viewed repeatedly to map recurring crisis discourse and governing practices. The analysis integrates dialogue and visual composition to identify discursive objects, authorized speakers, subject positions, and their practical effects as techniques of rule, including surveillance, scapegoating, crowd management, and decisions over protection and sacrifice. Results: Zona Merah frames the outbreak as a governance crisis, not only a biomedical event. Local elites control public announcements and TV narratives to shift blame and justify security measures that endanger citizens for elite continuity. Zaenal sustains dynastic power through institutions, media, and business networks, masked by welfare rhetoric. Dyah Ayu uses pastoral care and propaganda to manage consent and legitimize sacrifice, even at her faction’s expense. Media works as a regime of truth through “most wanted” framing that disciplines behavior via stigma and fear. Maya and Risang resist, but power also shapes social reality, limiting oppositional claims and systemic change. Conclusion: Zona Merah depicts crisis as a dispositif where power circulates through discourse, surveillance, and truth-production, enabling elite consolidation while positioning citizens as expendable. Implications: This study expands scholarship on Indonesian zombie cinema by showing how the genre can critique crisis governance, biopolitics, and media power in contemporary Indonesia.